Comparison of multiball training methods and guided training methods on student learning outcomes in table tennis courses - Jonas Solissa (Gladi : Jurnal Ilmu Keolahragaan, 2022)
The aims of this research are: 1). To find out differences in student learning outcomes in table tennis learning through the application of the Multiball and the Guided method, 2). To find out which method is better between the Multiball and the Guided method for student learning outcomes in Table Tennis courses. The subjects of this research were 32 male students of Physical Education, Sports and Recreation, University of Pattimura for the 2020/2021 Academic Year who offered Table Tennis courses. This research is a type of experimental research using a quantitative descriptive approach. The instrument used for data collection was a table tennis performance test. Based on the results of the research and data analysis, it shows that: 1) There is a difference, but not significant, in the student table tennis learning outcomes after being treated with the Multiball training method and the Guided training method. 2) There is no better method between the Multiball training method and the Guided training method.